Community Service thru Real Work Lecture in Sungai Kepayang Village, Senyerang District - Supriadi, Supriadi; Nisa, An; Marsela, Helen; Sasmika, Nanda; Suhaida, Suhaida; Nulipyeni, Riana; Bibet, Bibet; Marfuah, Marfuah; Solehah, Imratu; Nurdifanti, Afhia; Mardiyana, Mardiyana; Jani, Ariyan; Khusaini, Ahmad; Qauli, Ismayan; Komarudin, Komarudin; Bily, M. Arda; Solehudin, Solehudin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Community service thru the Real Work Lecture (KKN) is one form of implementing the Tri Dharma of Higher Education, aiming to enhance the role of students in supporting community development and empowerment. This article aims to describe the implementation and contribution of the KKN activities in Sungai Kepayang Village, Senyerang District, in the fields of education, religion, health, environment, and community social affairs. The methods used in this service activity are observation and direct participation of students in various work programs designed based on the needs of the village community. The activities carried out include religious teaching such as teaching Quran recitation, Yasinan, and Habshi activities; educational activities such as study guidance, teaching and learning activities (KBM) in schools, and the creation of prayer and intention guides for kindergarten/early childhood education; health and sports activities such as Posyandu and gymnastics; and social and environmental activities in the form of mutual cooperation, anti-bullying seminars, online sports and game tournaments, the creation of public facility signs, herbal gardens, biodegradable waste education boards, and village boundary markers. The results of the activity show an increase in community participation, the strengthening of religious and social values, and an increase in community awareness of health, education, and environmental cleanliness. Thus, the implementation of KKN in Sungai Kepayang Village has a positive impact in supporting village development and strengthening the role of students as agents of change in society.